Coherent Judaism : constructive theology, creation, & halakhah - Cherry, Shai (Brookline, MA : Academic Studies Press, 2020)
"Coherent Judaism begins by excavating the theologies within the Torah and tracing their careers through the Jewish Enlightenment of the eighteenth century. Any compelling, contemporary Judaism must cohere as much as possible with traditional Judaism and everything else we believe to be true about our world. The challenge is that over the past two centuries, our understandings of both the Torah and nature have radically changed. Nevertheless, much Jewish wisdom can be translated into a contemporary idiom that both coheres with all that we believe and enriches our lives as individuals and within our communities. Coherent Judaism explains why pre-modern Judaism opted to privilege consensus around Jewish behavior (halakhah) over belief. The stresses of modernity have conspired to reveal the incoherence of that traditional approach. In our post-Darwinian and post-Holocaust world, theology must be able to withstand the challenges of science and history. Traditional Jewish theologies have the resources to meet those challenges. Coherent Judaism concludes by presenting a philosophy of halakhah that is faithful to the covenantal aspiration to live long on the land that the Lord, our God, has given us"--
Frontmatter -- Contents -- Acknowledgments -- List of Abbreviations -- Timeline of Important Events -- Introduction -- Book One: A Partisan History of Jewish Theologies -- Preface -- 1. Priestly Religion -- 2. Mosaic Religion -- 3. Rabbinic Religiosity -- 4. The Medieval Centrifuge -- 5. The Modern Mix -- 6. Covenantal Judaism -- Book Two: Jewish Theologies of Creation -- Preface to Book Two -- 7. A Rabbinic Theology of Creation: Biblical Visions and Rabbinic Revisions -- 8 A Mystical Theology of Creation -- 9. Nature Read in Truth and Awe -- 10. Omnicide as Threat and Theodicy -- Book Three: Philosophies of Halakha -- Preface to Book Three -- 11. Turning Torah -- 12. Going Baroque -- 13. The Two Branches of a Divining Rod -- 14. The Shrinking Middle -- Conclusion: A Compelling Judaism -- Glossary -- Index of Names and Subjects -- Index of Sources
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on January 20, 2021).
In English.
eBooks on EBSCOhost
Keywords: Judaism; Judaïsme.; Judaism; RELIGION -- Judaism -- Theology; RELIGION / Judaism / Theology; Judaism